Memorial stone bearing an unpublished epigraph - Temples of India Project Team (Jio Institute, 2024)
The memorial stone, in the Government Museum Sikar, bears an unpublished epigraph recording the death of an individual named Mahipal. A niche carved on the top of the panel depicts a Shaiva ascetic on one side of a shivalinga and a devotee, likely perhaps Mahipal, standing on the other side. Though its precise provenance is unknown, this artifact sheds important information about the Shaiva landscape of the city of Sikar in the 12th century CE.